STRUCTURE AND CONDUCT OF LOCALLY MILLED RICE MARKET IN CENTRAL ZONE OF GOMBE STATE, NIGERIA - Adam, A.A.; Ya’u, A.; Bala, T.; Jaafar, I. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted to analyse the structure and conduct of locally milled rice marketing in Central Zone of Gombe State, Nigeria. A multi-stage sampling technique was used to arrive at the sample size for the study. Data for the study were collected using a semi-structured questionnaire and analysed using descriptive statistics, inferential statistics and Gini coefficient. The result of price determinants showed that demand and supply (70.7%), quality of grain (28.3 %) and transportation cost (1.1%) were the determinants of price in the market. Similarly, the result of market structure and conduct as presented by Gini Coefficient (0.72) and Lorenz curve plot indicates that there is high level of income inequality among the marketers. . Regression analysis also revealed that level of education (P<0.01), years of marketing experience (P<0.10), membership of market association (P<0.01), selling price (P<0.05) and amount of capital (P<0.10) were the significant factors influencing the profitability of marketers. The study concluded that locally milled rice market in the study area is characterized by features of imperfect market of monopolistic competition and marketers’ profitability is influenced by socio-economic variables. It is therefore recommended that Government and financial institutions should provide financial windows for marketers to easily acquire credit, marketers should leverage on existing market associations to demand necessary market facilities such as storage facilities from concerned authorities and Government should open up and rehabilitate rural roads to ease transportation and improve marketing efficiency.